Screening of Probiotic Bacteria Candidates in The Mangrove Tourism Area in Klawalu Sorong City West Papua - Sukmawati Sukmawati; M Iksan Badaruddin (UNIVERSITAS NEGERI PADANG, 2019)
Probiotic bacteria was one of the biological control agents (biological control). It had a role in suppressing or killing pathogenic microorganisms. In addition, it also played a role in improving water quality as in fish maintenance media. The basic principle of probiotics was the utilization of the ability of microorganisms to increase absorption in the digestive tract of fish. Probiotic bacteria were able to produce antimicrobial compounds such as lactic acid, hydrogen peroxide, bacteriocin. These compounds were antimicrobial and antibiotic that can suppress the growth of pathogenic bacteria. The purpose of this study was to detect candidate probiotic bacteria from the mangrove tourism area in Klawalu, Sorong City, West Papua. The results of screening for probiotic bacteria candidates by using selective media, from 16 samples consisting of water samples and mud samples’ obtained 11 positive samples, there were probiotic bacteria candidates with the bacterial morphological characteristics of each colony was almost similar. Keywords: Probiotic Bacteria, Mangrove Land, Sorong City